Guillain-Barré Syndrome in COVID-19: A Probable Association - Chaudhary, Ritesh; Bhandari, Rabin; Poudel, Masum; Giri, Rajani (Journal of BP Koirala Institute of Health Sciences, 2024)
Guillain–Barré syndrome (GBS) is characterized by  areflexia, albuminocytologic dissociation and progressive motor weakness. It has been associated with preceding viral infections. We report a case suggestive of a possible link between GBS and prior COVID-19 infection. A 20-year-old female from Dhankuta, with a history of COVID-19 infection diagnosed one month earlier, presented to the emergency department at B.P. Koirala Institute of Health Sciences (BPKIHS) with a two-day history of ascending paralysis. Based on the Brighton Criteria, a clinical diagnosis of GBS was suspected. In the context of the COVID-19 pandemic, GBS associated with SARS-CoV-2 infection should be carefully differentiated from other causes of neuropathy and myopathy. A high index of suspicion is essential for timely diagnosis and management.